The Nature of the Technetium Species Formed During the Oxidation of Technetium Dioxide with Oxygen and Water. Issue 9 (6th March 2018) - Childs, Bradley C.; Lawler, Keith V.; Braband, Henrik; Mast, Daniel S.; Bigler, Laurent; Stalder, Urs; Peterson, Derek R.; Jansen, Alek; Forster, Paul M.; Czerwinski, Kenneth R.; Alberto, Roger; Sattelberger, Alfred P.; et al.
Abstract : The oxidation of TcO2 with O2 in the presence of H2 O at 250 °C was investigated; Tc2 O7 and a red product were observed after the reaction. UV/Visible spectroscopy and a cerium titration on the "red" product are consistent with the presence of a reduced Tc species. It is proposed that the "red" product was formed by the hydrolysis of Tc2 O7 to HTcO4 followed by the reduction of HTcO4 . The reaction products of TcO2 with O2 /H2 O at 250 °C were also studied by mass spectrometry. The main dinuclear species were Tc2 O7 and Tc2 O5, while the main mononuclear species were TcO3 and HTcO4 . The compound HTcO4 and associated hydrates were simulated to identify candidate structures for the "red" product; however, neither the acid nor any related hydrates exhibited the UV/Visible signature of the "red" product. Abstract : The oxidation of TcO2 with O2 in the presence of H2 O at 250 °C was investigated; Tc2 O7 and a red product were observed after the reaction. Characterization was performed by using UV/Visible spectroscopy, electron impact mass spectrometry (EI‐MS) and theoretical methods.